AAV-mediated gene transfer to colon-innervating primary afferent neurons - Gore, Reshma; Esmail, Tina; Pflepsen, Kelsey; Marron Fernandez de Velasco, Ezequiel; Kitto, Kelley F.; Riedl, Maureen S.; Karlen, Andrea; McIvor, R. Scott; Honda, Christopher N.; Fairbanks, Carolyn A.; Vulchanova, Lucy (Frontiers in Pain Research, 2023)
Investigation of neural circuits underlying visceral pain is hampered by the difficulty in achieving selective manipulations of individual circuit components. In this study, we adapted a dual AAV approach, used for projection-specific transgene expression in the CNS, to explore the potential for targeted delivery of transgenes to primary afferent neurons innervating visceral organs. Focusing on the extrinsic sensory innervation of the mouse colon, we first characterized the extent of dual transduction following intrathecal delivery of one AAV9 vector and intracolonic delivery of a second AAV9 vector. We found that if the two AAV9 vectors were delivered one week apart, dorsal root ganglion (DRG) neuron transduction by the second vector was greatly diminished. Following delivery of the two viruses on the same day, we observed colocalization of the transgenes in DRG neurons, indicating dual transduction. Next, we delivered intrathecally an AAV9 vector encoding the inhibitory chemogenetic actuator hM4D(Gi) in a Cre-recombinase dependent manner, and on the same day injected an AAV9 vector carrying Cre-recombinase in the colon. DRG expression of hM4D(Gi) was demonstrated at the mRNA and protein level. However, we were unable to demonstrate selective inhibition of visceral nociception following hM4D(Gi) activation. Taken together, these results establish a foundation for development of strategies for targeted transduction of primary afferent neurons for neuromodulation of peripheral neural circuits.